2018
DOI: 10.3892/mmr.2018.8503
|View full text |Cite
|
Sign up to set email alerts
|

Cullin7 promotes epithelial‑mesenchymal transition of esophageal carcinoma via the ERK‑SNAI2 signaling pathway

Abstract: Cullin7 (CUL7) is a member of Cullin protein family and exhibits a tumor‑promoting role in several types of tumors, including breast, liver and ovarian. However, its roles in esophageal carcinoma (EC) have not yet been reported. In the present study, CUL7 expression in EC tissue was revealed to be significantly higher compared with nontumoral tissues, as detected by immunohistochemistry (IHC; P=0.000). χ2 analysis confirmed that CUL7 expression was positively associated with invasion depth (P=0.000), lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…CUL 7, Culin 7, is a component of an E 3 ubiquitin − proteinligase complex and interacts with p 53, CUL 9 and FBXW 8, and is reported to be an antiapoptotic oncogene 47 . CUL 7 has been associated with various cancer types, but its promotion of epithelial-mesenchymal transition in metastasis and its regulation of ERK − SNAI 2 signalling affecting the expression of cell adhesion proteins, E − cadherins , fibronectin , N − cadherin and vimentin in cancer is well studied 48 . CUL 7 inhibits apoptosis in lung cancer through inhibition of p 53 which regulates c − MYC cell cycle progression 47 .…”
Section: Discussionmentioning
confidence: 99%
“…CUL 7, Culin 7, is a component of an E 3 ubiquitin − proteinligase complex and interacts with p 53, CUL 9 and FBXW 8, and is reported to be an antiapoptotic oncogene 47 . CUL 7 has been associated with various cancer types, but its promotion of epithelial-mesenchymal transition in metastasis and its regulation of ERK − SNAI 2 signalling affecting the expression of cell adhesion proteins, E − cadherins , fibronectin , N − cadherin and vimentin in cancer is well studied 48 . CUL 7 inhibits apoptosis in lung cancer through inhibition of p 53 which regulates c − MYC cell cycle progression 47 .…”
Section: Discussionmentioning
confidence: 99%
“…A study in esophageal carcinoma (EC) showed that CUL7 protein expression was significantly higher than that in normal tissues, and was positively associated with tumor invasion and metastasis. An in vitro investigation demonstrated that CUL7 promotes the EMT of EC1 cells, indicating the mechanism of EC tumor metastasis 59 . Moreover, Zhi et al identified that CUL7 was able to differentiate the metastatic and non-metastatic colon cancer samples by using a support vector machine classifier 60 .…”
Section: Cul7 In Cancermentioning
confidence: 99%
“…These above studies show that CUL7 is associated with both proteolytic and non-proteolytic functional interactions. Notably, a recent study revealed that CUL7 could regulate the ERK-SNAI2 signaling pathway and promote EMT in EC 59 . However, whether CUL7 interacts with SNAI2 has not been studied.…”
Section: Cul7 Substrate Proteins In Development and Cancermentioning
confidence: 99%
“…CUL7, Culin7, is a component of an E3 ubiquitin-protein ligase complex and interacts with p53, CUL9 and FBXW8, and is reported to be an antiapoptotic oncogene (59). CUL7 has been associated with various cancer types, but its promotion of epithelial-mesenchymal transition in metastasis and its regulation of ERK-SNAI2 signalling affecting the expression of cell adhesion proteins, E-cadherins, fibronectin, N-cadherin and vimentin in cancer is well studied (60). CUL7…”
mentioning
confidence: 99%